Catch the Bus: Probing Other-Than-Human Perspectives in Design Research - Bedö, Viktor (Frontiers in Computer Science, 2021)
Prompted by Catch the Bus, an experimental street game design project with and for autonomous buses, this text explores strategies to substantiate the speculation about other-than-human perspectives. It builds on philosophical arguments about the role of species similarity in grasping non-human experience and applies these arguments to thing perspectives. Gameplay and props from Catch the Bus instantiate a kind of similarity between human players and autonomous buses that emerges through the adoption of certain choreographies and sensing capabilities. The text contributes theoretical arguments to the debate of other-than-human perspectives in more-than-human design.